2014
DOI: 10.1523/jneurosci.1288-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Does Trans-Spinal Direct Current Stimulation Alter Phrenic Motoneurons and Respiratory Neuromechanical Outputs in Humans? A Double-Blind, Sham-Controlled, Randomized, Crossover Study

Abstract: Although compelling evidence has demonstrated considerable neuroplasticity in the respiratory control system, few studies have explored the possibility of altering descending projections to phrenic motoneurons (PMNs) using noninvasive stimulation protocols. The present study was designed to investigate the immediate and long-lasting effects of a single session of transcutaneous spinal direct current stimulation (tsDCS), a promising technique for modulating spinal cord functions, on descending ventilatory comma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 83 publications
3
35
1
6
Order By: Relevance
“…iTBS is routinely performed non-invasively using TMS (Huang et al, 2005). tsDCS is non-invasive and has been performed safely in human cervical spinal cord for modulating respiratory function (Niérat et al, 2014). A potential advantage of the “open loop” neuromodulatory approach used in this study is that it does not depend on the timing of critical neural events, such as with paired associative stimulation (Thickbroom, 2007), or on the occurrence of motor event, such as in “closed loop” stimulation paradigms (e.g., (McPherson et al, 2015)).…”
Section: Discussionmentioning
confidence: 99%
“…iTBS is routinely performed non-invasively using TMS (Huang et al, 2005). tsDCS is non-invasive and has been performed safely in human cervical spinal cord for modulating respiratory function (Niérat et al, 2014). A potential advantage of the “open loop” neuromodulatory approach used in this study is that it does not depend on the timing of critical neural events, such as with paired associative stimulation (Thickbroom, 2007), or on the occurrence of motor event, such as in “closed loop” stimulation paradigms (e.g., (McPherson et al, 2015)).…”
Section: Discussionmentioning
confidence: 99%
“…Another study that did examine motor responses during cervical tsDCS showed an increase in diaphragm MEPs (Niérat et al . ). Thus, we tested both MEPs and CMEPs in the upper limb during the application of cervical tsDCS.…”
Section: Discussionmentioning
confidence: 97%
“…C, averaged eCMEPs and mCMEPs (10-15 traces) for a single participant (upper traces are eCMEPs, and examine these potentials during stimulation (Dongés et al 2017). Another study that did examine motor responses during cervical tsDCS showed an increase in diaphragm MEPs (Niérat et al 2014). Thus, we tested both MEPs and CMEPs in the upper limb during the application of cervical tsDCS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations